2023
DOI: 10.3389/fncel.2023.1188672
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor (BDNF) has direct anti-inflammatory effects on microglia

Abstract: Microglia are the primary immunocompetent cells that protect the brain from environmental stressors, but can also be driven to release pro-inflammatory cytokines and induce a cytotoxic environment. Brain-derived neurotrophic factor (BDNF) is important for the regulation of plasticity, synapse formation, and general neuronal health. Yet, little is known about how BDNF impacts microglial activity. We hypothesized that BDNF would have a direct modulatory effect on primary cortical (Postnatal Day 1-3: P1-3) microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…4 G, H). BDNF has been reported to exhibit direct modulatory effects on LPS-induced inflammation in both microglia and neuronal cultures [ 9 ]. Furthermore, in vivo studies have demonstrated that the administration of pro-inflammatory cytokines or lipopolysaccharide (LPS) significantly reduces mature BDNF levels in brain regions such as the hippocampus and cerebral cortex [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 G, H). BDNF has been reported to exhibit direct modulatory effects on LPS-induced inflammation in both microglia and neuronal cultures [ 9 ]. Furthermore, in vivo studies have demonstrated that the administration of pro-inflammatory cytokines or lipopolysaccharide (LPS) significantly reduces mature BDNF levels in brain regions such as the hippocampus and cerebral cortex [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It plays a critical role in maintaining neuroplasticity and regulating neuronal development, differentiation, and survival. Pro-inflammatory cytokines or lipopolysaccharide (LPS) has been demonstrated to significantly reduce mature BDNF levels in brain regions, including hippocampus [ 9 ]. Recent research has further linked BDNF/TrkB signaling to depression.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral BDNF concentrations are positively correlated with hippocampal size and cognitive function [196,197]. Similarly, the evidence points to the potential anti-inflammatory properties of BDNF on the brain [198][199][200]. Thus, one may speculate on how mindfulness could increase BDNF in the context of methamphetamine dependency.…”
Section: Neurotrophic and Vascular Effect Of Mindfulness On Neuroplas...mentioning
confidence: 95%
“…Despite previous studies indicating a strong involvement of BDNF in the nociceptive system, its precise role remains uncertain. This uncertainty is further compounded by conflicting findings, with some research indicating a potential anti-inflammatory effect [118][119][120]. For instance, preliminary evidence from animal research suggests that the release of BDNF can alleviate allodynia and hyperalgesia induced by chronic constriction injury [121].…”
Section: Pro-nociceptive and Anti-nociceptive Role Of Bdnfmentioning
confidence: 99%